Pengaruh Pemahaman Perpajakan, Kualitas Pelayanan dan Pengawasan Terhadap Penerimaan Pajak Restoran Pada Badan Pendapatan Daerah (Bapenda) Kabupaten Bandung II Soreang - Nuraeni, Ranti; Saepuloh, Cepi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
Restaurant tax is a key source of Local Own-Source Revenue (PAD) that supports regional development. However, its realization in Bandung Regency II Soreang remains suboptimal. This study aims to analyze the effect of tax understanding, service quality, and supervision on restaurant tax revenue. A quantitative method with an associative approach was used. Data were collected through questionnaires from 95 restaurant taxpayers. Data analysis techniques include validity and reliability tests, classical assumption tests (normality, multicollinearity, and heteroscedasticity), multiple linear regression, partial (t-test) and simultaneous (F-test) significance tests, and coefficient of determination (R²). The results show that tax understanding, service quality, and supervision have a positive and significant effect, both partially and simultaneously, on restaurant tax revenue. These findings highlight the importance of improving tax education, optimizing service quality, and strengthening supervision systems to enhance taxpayer compliance and local tax revenue.